2013
DOI: 10.1093/tropej/fmt072
|View full text |Cite
|
Sign up to set email alerts
|

Yield of Screening for TB and HIV among Children Failing to Thrive in Botswana

Abstract: TB and HIV screening among children with FTT diagnosed TB in 6% of cases completing an evaluation, but no new HIV infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…The reason for these findings is not apparent but are similar to those reported in a study in western Kenya [27]. In children, the additional symptoms required for screening, such as failure to thrive, and lethargy were sub-optimally documented, showing missed opportunities for actively looking for TB among them, which has been evidenced to detect TB cases [29]. The IPT completion rates in Kenya were above 95%, which is higher compared to other African countries, where it ranges from 70-94% [30][31][32].…”
Section: Plos Onesupporting
confidence: 74%
“…The reason for these findings is not apparent but are similar to those reported in a study in western Kenya [27]. In children, the additional symptoms required for screening, such as failure to thrive, and lethargy were sub-optimally documented, showing missed opportunities for actively looking for TB among them, which has been evidenced to detect TB cases [29]. The IPT completion rates in Kenya were above 95%, which is higher compared to other African countries, where it ranges from 70-94% [30][31][32].…”
Section: Plos Onesupporting
confidence: 74%
“…7 Paediatric inpatient programmes were the most common context (17), 6,7,10,[13][14][15][16][17][18][19][21][22][23][24][25]29,30 followed by nutrition centres (four), 9,11,12,27 EPI centres (three), 20 programmes (three). 8,20,31 The assessment for quality showed that most of the included studies (20) [9][10][11][12][15][16][17][18][19][20][22][23][24][25][26][27][28][29][30][31] were of fair or good quality and the remainder (six) [6][7][8]13,…”
Section: Resultsmentioning
confidence: 99%
“…We did a stratifi ed analysis of paediatric HIV prevalence in southern and eastern Africa (20 studies) 8,[10][11][12][13][14][15][16][17][18][19][20][21][22][24][25][26][27]28,29 versus that in west and central Africa (four). 9,23,28,31 Paediatric HIV prevalence across contexts in southern and eastern Africa was 17·8% (95% CI 12·8-22·7) and prevalence in west and central Africa was 9·8% (95% CI 4·2-15·3).…”
Section: Resultsmentioning
confidence: 99%
“…In Botswana, approximately half of children diagnosed with TB are reported to have concurrent failure to thrive (including undernutrition and malnutrition) and one study found that 6% of children with failure to thrive had concurrent TB. 10 Failure to thrive is thus a critical red flag for young children in endemic areas and should elicit prompt TB screening. Earlier recognition of failure to thrive may have led to an earlier diagnosis in the case of the infant described.…”
Section: Global Health Problem Analysismentioning
confidence: 99%